2018
DOI: 10.1080/1331677x.2018.1523740
|View full text |Cite
|
Sign up to set email alerts
|

The macroeconomic effects of transport infrastructure on economic growth: the case of Central and Eastern E.U. member states

Abstract: This paper empirically investigates the effects of transport infrastructure on economic growth in Central and Eastern European Member States (C.E.M.S.) in the period 1995-2016. During the transition period in C.E.M.S., most investments were focused on the roads, while railways have been lagging for decades. The aim of this paper is to estimate the effects of transport infrastructure (road and rail) on economic growth while controlling with other variables such as population growth, gross fixed capital formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 30 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…Investment in transportation infrastructure has been recognized as a crucial growth-promoting strategy (Crescenzi et al 2016 ). Some recent studies have validated this conclusion on the symmetric impacts of transport infrastructures on economic growth, and these include Kauzen et al ( 2020 ) for Tanzania, Kalan and Gokasar ( 2020 ) for Turkey, Popov ( 2020 ) for Russia, Hanedar and Uysal ( 2020 ) for the Ottman Empire, Babatunde ( 2018 ) for Nigeria, Stawiarska ( 2018 ) for Poland, Cigu et al ( 2019 ) and Vlahinić Lenz, et al ( 2018 ) for European Union (EU) economies and Xueliang ( 2013 ) for China. In India, studies that have found either mutual feedbacks between road infrastructure and economic growth or a unidirectional causality from rail infrastructure to economic growth include Pradhan and Bagchi ( 2013 ) and Vidyarthi and Mishra ( 2020 ).…”
Section: An Overview Of the Empirical Literaturementioning
confidence: 81%
“…Investment in transportation infrastructure has been recognized as a crucial growth-promoting strategy (Crescenzi et al 2016 ). Some recent studies have validated this conclusion on the symmetric impacts of transport infrastructures on economic growth, and these include Kauzen et al ( 2020 ) for Tanzania, Kalan and Gokasar ( 2020 ) for Turkey, Popov ( 2020 ) for Russia, Hanedar and Uysal ( 2020 ) for the Ottman Empire, Babatunde ( 2018 ) for Nigeria, Stawiarska ( 2018 ) for Poland, Cigu et al ( 2019 ) and Vlahinić Lenz, et al ( 2018 ) for European Union (EU) economies and Xueliang ( 2013 ) for China. In India, studies that have found either mutual feedbacks between road infrastructure and economic growth or a unidirectional causality from rail infrastructure to economic growth include Pradhan and Bagchi ( 2013 ) and Vidyarthi and Mishra ( 2020 ).…”
Section: An Overview Of the Empirical Literaturementioning
confidence: 81%
“…Bensassi, Márquez Ramos [ 26 ] highlighted that logistics measures are important at the regional level and the number, size and quality of logistics facilities have a beneficial positive impact on export flows. Therefore, it is critical to invest in the development of railway infrastructure in the Central and Eastern European Member States to assure long-term transport efficiency, establish competitive advantages, and consequently stimulate long-term economic growth [ 27 ]. Saidi, Mani [ 28 ] too reveals that increases in transport infrastructure results in enhanced economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Boopen, in a study [36], analyzing the contribution of transportation investment to development in 38 Sub-Saharan African countries, concluded that transportation had been a contributor to the economic progress of these countries. Vlahinic Lenz et al also proved that infrastructure plays an essential role in driving economic growth in Central and Eastern European Member States, [37]. In line with those findings, the results of [38] are the same for the case of East Asia.…”
Section: Development Of Infrastructure Investmentmentioning
confidence: 64%